2008
DOI: 10.1037/a0012600
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of stereotypies in juvenile monkeys (Macaca mulatta) with neonatal amygdala or hippocampus lesions.

Abstract: The emergence of stereotypies was examined in juvenile rhesus monkeys who, at two weeks of age, received selective bilateral ibotenic acid lesions of the amygdala (N=8) or hippocampus (N=8). The lesion groups were compared to age-matched control subjects that received a sham surgical procedure (N=8). All subjects were maternally reared for the first six months and provided access to social groups throughout development. Pronounced stereotypies were not observed in any of the experimental groups during the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
40
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 57 publications
4
40
3
Order By: Relevance
“…The HI paradigm has been proven to be a robust task for identifying anxious temperament (Kalin, et al, 2001; Fox, et al, 2008; Oler, et al, 2010; Shackman, et al, 2013), and may be more sensitive for detecting anxiety-like behaviors than social interaction observations or reactions to novel objects used in earlier studies. Contrary to previous studies indicating Neo-Hibo lesions increased motor stereotypies, with no difference in self-directed behaviors (Bauman, et al, 2008), the current study showed the reverse, i.e. no differences in stereotypies, and increased self-directed behaviors (self-grooming and self-clasping) during both infancy and adulthood.…”
Section: Discussioncontrasting
confidence: 99%
“…The HI paradigm has been proven to be a robust task for identifying anxious temperament (Kalin, et al, 2001; Fox, et al, 2008; Oler, et al, 2010; Shackman, et al, 2013), and may be more sensitive for detecting anxiety-like behaviors than social interaction observations or reactions to novel objects used in earlier studies. Contrary to previous studies indicating Neo-Hibo lesions increased motor stereotypies, with no difference in self-directed behaviors (Bauman, et al, 2008), the current study showed the reverse, i.e. no differences in stereotypies, and increased self-directed behaviors (self-grooming and self-clasping) during both infancy and adulthood.…”
Section: Discussioncontrasting
confidence: 99%
“…By 18 months of age, hippocampus-lesioned animals were more active than control subjects. This is consistent with the hypermotoric behavior that we have documented with these animals in social settings (Bauman et al, 2008; Lavenex, et al, 2008) and with evidence from other research groups who have demonstrated hyperactivity in hippocampus-lesioned adult macaques (e.g., Machado & Bachevalier, 2006). …”
Section: Discussionsupporting
confidence: 91%
“…Raw data are presented here for the purposes of interpretation; log transformed data are available upon request. For the sake of analytic continuity with previous reports on these subjects (Bauman et al, 2004a; Bauman et al, 2008) and in order to establish an understanding of the developmental trajectory of specific behaviors, ANOVAs were conducted on individual behaviors. In some cases, the omnibus test did not reach conventional levels of significances, but visual inspection of each group’s marginal means suggested that there were significant differences between two of the three groups.…”
Section: Methodsmentioning
confidence: 99%
“…The role of the amygdala in normal social and affective development, however, has received less attention as only a few laboratories have undertaken developmental studies following early amygdala damage (e.g., Thompson, Schwartzbaum, & Harlow, 1969; Thompson & Towfighi, 1976; Thompson, Bergland, & Towfighi, 1977, Beauregard, Malkova, & Bachevalier, 1995; Bachevalier, Alvarado, & Malkova, 1999; Bachevalier & Beauregard, 1999; Goursaud & Bachevalier, 2007; Goursaud, Wallen, & Bachevalier, 2014; Raper, Stephens, Sanchez, Bachevalier, & Wallen, 2014; Stephens, Raper, Bachevalier, Wallen, 2014; Bauman, Lavenex, Mason, Capitanio, & Amaral, 2004a; Bauman, Lavenex, Mason, Capitanio, & Amaral, 2004b; Bauman, Toscano, Mason, Lavenex, & Amaral, 2006; Bauman, Toscano, Babineau, Mason, & Amaral, 2008; Bliss-Moreau, Toscano, Bauman, Mason, & Amaral, 2010; Bliss-Moreau, Toscano, Bauman, Mason, & Amaral, 2011; Bliss-Moreau, Bauman, & Amaral, 2011; Bliss-Moreau, Moadab, Bauman, & Amaral, 2013). As part of an ongoing study, we evaluated social behavior at a critical developmental time point—the transition to adulthood—in a cohort of female rhesus macaques who received neonatal damage to the amygdala.…”
mentioning
confidence: 99%
See 1 more Smart Citation